Comparing student understanding of quantum physics when embedding multimodal representations into two different writing formats: Presentation format versus summary report format - (:unkn) unknown (WILEY, 2006)
Physics as a subject for school students requires an understanding and ability to move between different modes of representation for the concepts under review. However, the inability of students to have a multimodal understanding of the concepts is seen as restricting their understandings of the concepts. The aim of this study was to explore the effectiveness of using writing-to-learn strategies that required students to embed multimodal representations of the concepts. In particular, the study compared a presentation format with a summary report format for students learning quantum theory. A pre-post test design was used to compare performances of these two groups across two units. For unit 1, students' scores from groups that completed either a presentation format (PowerPoint presentation) or a summary report format (chapter summary) were compared. No limits were placed on the amount of text or the number of representations used. For unit 2, products of both groups were constructed for an audience of year 10 students. The presentation format group (PowerPoint) was limited to 15 slides, with a maximum of 10 words displayed per slide; a script was written to accompany the presentation. Slides could include graphical and mathematical formulae; however, the text could not. The summary report format group that wrote out its explanations was limited to four pages and was required to incorporate multimodal representations. Results indicated that for both units students using the presentation format group scored significantly better on tests than the summary report format group. The effect size difference between the groups increased for the second unit, indicating that more practice was leading to better student understanding of the physics concepts. (c) 2006 Wiley Periodicals, Inc.
Keywords: SECONDARY SCIENCE; LITERACY; PSYCHOLOGY; CLASSROOM; EFFICACY; LANGUAGE; DESIGN